The Role of the Church in Providing Motivation to People with Disabilities through Special Worship Services for Parents and Children at the HKBP Jatiasih Congregration, Bekasi - Siregar, Julinda; Sihotang, Hotmaulina (Asian Journal of Community Services, 2024)
The special service for people with disabilities in HKBP Jatiasih is a form of attention to motivate parents to remain enthusiastic in accompanying their children even though they have disabilities. HKBP Jatiasih, especially the Diakonia Team, want to make this activity has an impact on other churches paying attention to congregations with disabilities. Disabled worship services are held once every 3 months, provides a service of words delivered by the Pastor and then prepares blessings in the form of money and food. This activity has been carried out for more than 2 years, which is included in the program for the Year of Health, the Year of Professionalism in Service Organizers, and the Year of Inclusive Ecumenical 2024.